PENGARUH GEL PUTIH TELUR BEBEK TERHADAP PENYEMBUHAN LUKA INSISI PADA MENCIT (Mus musculus) - Mahendra Mahendra; Abdul Karim; Arman Ismail; Lasmaria Flora Roslinda Silaen (Collaborative Medical Journal, 2023)
Skin injuries are a common health problem and can be caused by various factors such as injury or surgery. The skin is the body's first defense against microorganisms and chemicals, so wounds on the skin can cause damage to tissues. The prevalence of wounds in Indonesia increased from 7.5% in 2012 to 8.2% in 2013. Traditional medicine is still widely used by the people, and eggs have potential as an effective alternative treatment because they are rich in protein and amino acids needed to form new tissues and speed up the healing process. Based on searches on PubMed, there has been no research on the relationship between duck egg whites to incision wound healing. Analyze the effect of duck egg white gel on the healing of incision wounds in mice. The study was an experimental study with a Posttest only with Control Group design, involving twenty mice that were divided into four groups: a positive control group using povidone iodine, a negative control group using a gel base, and two treatment groups. The remaining length of the wound was measured every 2 days using calipers on days 3, 5, and 7. The results of the study showed a p-value of <0.05, indicating that duck egg white gel at both 10% and 20% concentrations was effective in accelerating the healing of incision wounds in mice. The duck egg white gel at a concentration of 20% exhibited the most significant effectiveness in promoting the healing of incision wounds in mice